THE USE OF SOIL MERCURY AND RADON GAS SURVEYS TO ASSIST THE DETECTION OF CONCEALED FAULTS IN FUZHOU CITY, CHINA - Wang G.; Liu Ch.; Wang J.; Liu W.; Zhang P. (My University, 2006)
Soil gas approaches have been proven useful for detecting buried faults in field survey. How about their applicability in urban area? A trial soil gas survey has been conducted in an attempt to evaluate this in Fuzhou City, Southeastern China. The detection was performed by measuring the adsorbed mercury, free mercury and radon gases in soil in the sites such as crop soil, refilled soil and those with shallow groundwater levels. The resulting distributions show that anomalous concentrations of soil gases over faults are generally two to four times as much as those in the surrounding areas. The locations of peak values of absorbed and free mercury could possibly be applied to assist to determine the trend of faults. The background values of free mercury seems to be more stable and the anomalous zones narrower than those of radon gas, therefore, the free mercury method seems to be good for detection at this area, especially in those sites with shallow groundwater levels. The false gas anomalies may occur in such a site as refilled with external soil, refilled pond and abandoned construction bases.
Keywords: SOIL GAS; CONCEALED FAULT; URBAN AREA; CHINA